THE STUDY OF TEACHER TALK AND STUDENT TALK IN SPEAKING CLASS - ida yulianawati (Wiralodra English Journal, 2018)
The paper concerns with investigating classroom interaction especially the classroom language used by teacher and students in teaching learning process in one Junior High School in Indramayu. Teacher’s talk signals the classroom language that is used by the teacher in the classroom throughout the class periods. Meanwhile, students’ talk signal classroom language that is used by the students. The study employs qualitative interaction analysis method involving fifty nine students and two teachers in two different classrooms. The data are gathered through non-participant observation and video recording. Classroom observations were conducted to gain the data concerning classroom interaction in teaching learning process. The data collecting was separated into twelve categories and analyzed using Flint (Foreign Language Interaction analysis) system adopted from Moscowitz that is widely used to investigate classroom interaction. The findings of this study showed that there are various verbal interactions used in classroom interaction. The data showed that the use of classroom language motivate students to speak and encourage the students to share their idea. But the data also showed that there are many obstacles in using classroom language. So it needs more effort from teachers and students to make classroom language familiar in the classroom.